Identifying emergent agent types and effective practices for portability, scalability, and intercomparison in water resource agent-based models. (May 2020) - Kaiser, Kendra E.; Flores, Alejandro N.; Hillis, Vicken
Abstract: Modeling coupled social and biophysical dynamics of water resources systems is increasingly important due to population growth and changes in the water cycle driven by climate change. Models that explicitly represent these coupled dynamics are challenging to design and implement, particularly given the complicated and cross-scale nature of water governance. Agent-based models (ABMs) can capture human decision-making and nested social hierarchies, however, transferability is made difficult by location-specific details. A consistent description of water resources decision-makers (individuals, groups, agencies) would advance the rate of model development and increase synthesis across systems. Reviewing water resources ABMs, we propose eight agent types and associated operational roles that modify the storage, redistribution, and water use in a system. Application of the proposed typologies and use of best practices in model documentation, will support systematic design and development of transferable, scalable, water resources ABMs and facilitate the dynamic coupling of social and biophysical process modeling. Highlights: Agent based models are powerful tools for simulating complex water resource systems. Common typologies emerged from a review of water resources agent-based models. Functional definitions of agents and their roles can increase model transferability. Conceptualizing agent types as class objects can clarify connectivity between agents. Defining agents functionally clarifies connections between agents and the environment